2012
DOI: 10.1002/pen.23344
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ester‐amine) hyperbranched polymer as toughening and co‐curing agent for epoxy/clay nanocomposites

Abstract: The marriage between hardness and flexibility of epoxy resins (improved toughness) is a desired feature, which broads their application in various industrial fields, especially for high impact resistance purposes. Accordingly, this work aims to improve toughness properties of epoxy resin (Epon‐828)/Ancamine (curing agent) system using amino‐terminated hyperbranched poly(ester‐amine) [Poly(PEODA‐NPA)] (HP) as toughening and/or co‐curing agent, in presence of organo‐modified Montmorillonite clay (OMMT) as a rein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…HBPs have attracted considerable attention as modifiers of epoxy resins, principally for the purposes of toughening [ 13 19 ], though their effects on the morphology [ 20 22 ] and on other properties, such as the cure kinetics [ 23 25 ] and the thermal expansion coefficient and microhardness, have also been investigated [ 26 ]. The study of HBPs in epoxy composites in general [ 27 ] and in nanocomposites in particular has been more limited, most studies being on polyurethane nanocomposites [ 28 35 ], although there have been some studies on HBPs in epoxy-based nanocomposites systems [ 36 38 ], in which the epoxy is usually DGEBA.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…HBPs have attracted considerable attention as modifiers of epoxy resins, principally for the purposes of toughening [ 13 19 ], though their effects on the morphology [ 20 22 ] and on other properties, such as the cure kinetics [ 23 25 ] and the thermal expansion coefficient and microhardness, have also been investigated [ 26 ]. The study of HBPs in epoxy composites in general [ 27 ] and in nanocomposites in particular has been more limited, most studies being on polyurethane nanocomposites [ 28 35 ], although there have been some studies on HBPs in epoxy-based nanocomposites systems [ 36 38 ], in which the epoxy is usually DGEBA.…”
Section: Introductionmentioning
confidence: 99%
“…The supposed advantages of incorporating an HBP in the nanocomposite system are both to improve the dispersion of the clay in the epoxy resin matrix and also to increase the degree of exfoliation that takes place when the system is cured. In this respect, we review briefly the results reported in [ 36 38 ]. In the work of Becker et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of solvents in proceeding the preparation is environmentally good and makes the process more suitable for industrialization . Heretofore, a wide variety of compounds have been intercalated in MMT by ion‐dipole interaction, such as amines, aniline salts, aldehydes, alcohols, imidazoles, block copolymers, epoxy resin, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Several types of hyperbranched polymers were prepared such as polyphenylenes, polyethers, polyesters, polyamides, polycarbonates, poly(ether ketones), and polyurethanes [6][7][8][9][10][11][12]. Generally, hyperbranched polymers are readily feasible for different potential applications, such as toughening and cocuring agents, multifunctional initiators, rheology control compounds for surface modification, medical applications, nanofillers for polymer nanocomposites, nonlinear optics, nanoporous generators for low dielectric constant insulators, coatings, and drug delivery systems [13][14][15][16][17][18][19][20][21][22][23][24]. Therefore, hyperbranched polymers are of immense importance for industrial applications.…”
Section: Introductionmentioning
confidence: 99%